Efforts to Increase Students' Problem-Solving Abilities Through the Application of PBL Assisted by Virtual Laboratory on the Hydrostatic Pressure Concept - Indrawati Lasumbu; Dewi Diana Paramata; Tirtawaty Abdjul; Abdul Haris Odja; Dewa Gede Eka Setiawan; Wahyu Mu’zizat Mohamad (Postgraduate, University of Mataram, 2024)
This research aims to enhance the problem-solving abilities of class XI students at MAS Wahdah Islamiyah Tilongkabila using a problem-based learning (PBL) model through the Classroom Action Research method. The collected data includes students' problem-solving abilities, student activities, and teacher activities. The instruments used were observation sheets for teacher and student activities, final tests (post-tests) on students' problem-solving abilities, and interviews. The average percentage of teacher activity observations increased from 65.6% in cycle I to 93.7% in cycle II, marking a 28.1% improvement. Student activity rose from an average of 56.75% in cycle I to 89% in cycle II, reflecting a 32.2% increase. Additionally, students' problem-solving abilities improved from an average of 58.6% in cycle I to 84.3% in cycle II, a 25.7% increase. The application of PBL, assisted by a virtual laboratory on the concept of hydrostatic pressure, significantly enhances students' problem-solving skills.